2015
DOI: 10.1297/cpe.24.69
|View full text |Cite
|
Sign up to set email alerts
|

Single serum cortisol values at 09:00 h can be indices of adrenocortical function in children with Kawasaki disease treated with intravenous immunoglobulin plus prednisolone

Abstract: Combination treatment with intravenous immunoglobulin (IVIG) plus prednisolone is effective for prevention of cardiovascular complications in children with Kawasaki disease (KD). However, administration of prednisolone for approximately 20 d in this regimen causes adrenocortical suppression in a high proportion of treated children. To establish a simple method to screen for this suppression, we performed a prospective study on 72 children with KD treated with this regimen in our institution from February 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Based on peak cortisol values from the CRH stimulation test, all subjects as well as those in primary disease groups (IBD, purpura, West syndrome, and others) were further divided into two subgroups. One group had insufficient adrenal function (peak cortisol values < 15 µg/dL) and the other with intact adrenal function (peak cortisol values > 15 µg/dL), in accordance with the definition applied in our previous study ( 8 ). Scatter diagrams were then constructed, and the overlap of the two subgroups was calculated.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…Based on peak cortisol values from the CRH stimulation test, all subjects as well as those in primary disease groups (IBD, purpura, West syndrome, and others) were further divided into two subgroups. One group had insufficient adrenal function (peak cortisol values < 15 µg/dL) and the other with intact adrenal function (peak cortisol values > 15 µg/dL), in accordance with the definition applied in our previous study ( 8 ). Scatter diagrams were then constructed, and the overlap of the two subgroups was calculated.…”
Section: Methodssupporting
confidence: 83%
“…1B, C, E ). This may be one reason why the degrees of AUC in these categories were not as high as that in subjects with West syndrome or Kawasaki disease ( 8 ). We could not get satisfactorily high degrees of AUC from ROC curves even when we divided our subjects (excluding patients with West syndrome) into subgroups according to the duration of initial treatment (data not shown).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In an interventional study where a high-dose, short-term glucocorticoid (HDC 25 mg twice daily for five days) was administered to healthy adult subjects, the peak cortisol response to the ITT significantly decreased two days after PSL discontinuation but nearly returned to pretreatment levels five days after the intervention [72]. An observational study of childhood asthma found that adrenal function normalized in all 11 patients ten days after the completion of short-term PSL treatment [30], and another study of PSL treatment for Kawasaki disease in children reported recovery in more than half the patients within two months [67].…”
Section: Short-term Administrationmentioning
confidence: 99%
“…A reference value of plasma cortisol, which is equivalent to that of serum cortisol [63][64][65], ≤3 µg/dL (83 nmol/L), may indicate SIAI, while a value >19 µg/dL (525 nmol/L) can be used to exclude SIAI [66]. A cohort study suggested a serum cortisol level of 5 µg/dL at 9 a.m. in children as a cutoff value for SIAI screening following steroid administration for Kawasaki disease [67].…”
Section: Early Morning Serum Cortisol Levelmentioning
confidence: 99%